Um Framework Conceitual para Interoperabilidade Pragmática - Ribeiro, Elivaldo Lozer Fracalossi; Monteiro, Erasmo Leite; Claro, Daniela Barreiro; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Interoperability is the ability of heterogeneous systems to communicate with another system transparently. Usually, interoperability is classified into syntactic, semantic, and pragmatic. The syntactic level is related to the grammar and vocabulary of the message swapped, the semantic level with the meaning of the data and the pragmatic level with the understanding of the messages sent and received. A set of systems is pragmatically interoperable when they share the same expectations about the effect of messages exchanged between them. Due to the vast diversity of definitions and no consensus, provide a pragmatic interoperability solution is a challenge. In this paper, we propose a conceptual framework that aims to contribute to the unification of the concept of pragmatic interoperability and common elements necessary for its realization. For this, a unified definition and conceptual framework are presented. The framework was applied in three different scenarios to demonstrate its applicability and, consequently, validation of the unified concept.